2021
DOI: 10.3389/fimmu.2021.703457
|View full text |Cite
|
Sign up to set email alerts
|

Non-HLA Antibodies and Epitope Mismatches in Kidney Transplant Recipients With Histological Antibody-Mediated Rejection

Abstract: BackgroundCorrelation between antibody-mediated rejection (ABMR) and circulating HLA donor-specific antibodies (HLA-DSA) is strong but imperfect in kidney transplant (KT) recipients, raising the possibility of undetected HLA-DSA or non-HLA antibodies contributing to ABMR. Detailed evaluation of the degree of HLA matching together with the identification of non-HLA antibodies in KT may help to decipher the antibody involved.MethodsWe retrospectively assessed patients with transplant biopsies scored following Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 54 publications
1
29
1
1
Order By: Relevance
“…Allograft survival rates were similar between DSA-negative ABMR and DSA-positive ABMR. Like us, Crespo et al and Sablik et al described a lack of association between DSA status and allograft survival in the presence of ABMR (11,13). However, our results disagree with those of Senev et al, who suggested that the risk of allograft failure was significant lower for patients with DSA-negative ABMR than for those with DSA-positive ABMR (12).…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…Allograft survival rates were similar between DSA-negative ABMR and DSA-positive ABMR. Like us, Crespo et al and Sablik et al described a lack of association between DSA status and allograft survival in the presence of ABMR (11,13). However, our results disagree with those of Senev et al, who suggested that the risk of allograft failure was significant lower for patients with DSA-negative ABMR than for those with DSA-positive ABMR (12).…”
Section: Discussioncontrasting
confidence: 96%
“…However, several reports have documented the histologic picture of ABMR in the absence of detectable DSAs (11)(12)(13)(14)(15)(16)(17). Circulating DSAs in the presence of ABMR-compatible histologic lesions were absent in as many as 27% of patients with ABMR (12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the relationship with rejection has not been proven, because we did not find any case of BPR. These findings are similar to those found by Crespo et al, who showed no association between post-transplant AT1R-Ab and HLA-DSA detection or biopsy-proven anti-body-mediated rejection [28].…”
Section: Discussionsupporting
confidence: 92%
“…Endothelin A receptor (ETA receptor) is now considered one of the non-HLA antigens, which may be a significant trigger in immunological response and graft loss [ 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%